Online transparency and corporate governance in Spanish governmental agencies. Issue 4 (12th August 2019) - Pina, Vicente; Torres, Lourdes
Abstract : Purpose: Online transparency has become a tool to increase legitimacy and trust in governments. The purpose of this paper is to study the online transparency of Spanish Central Government agencies and analyze whether their corporate governance (CG) structures influence their online transparency. Design/methodology/approach: The information used for building an online transparency index and about the board of directors has been collected from the websites of the 168 agencies and from their statutes and activity reports. Ordinary least squares analysis is used. Based on a previous literature review and the requirements of the EU Directive and Spanish legislation, 108 items included in the websites have been analyzed. Findings: The average information displayed through the website agencies is significantly less than the information considered as relevant in previous literature and in the Spanish legislation. The highest values are presented by the technical dimensions and the lowest by the organizational/political dimension. The presence of independent directors and women on the boards of directors are revealed as the most important explanatory factors of online transparency. Practical implications: Practical implications to improve online transparency are related to the organizational/political dimension – including the positions and CVs of members of governing bodies, minutes, etc. and to the presence of independent directors and, to a lesser extent, of women, on the board of directors. Originality/value: The contribution of this paper is the identification of some online transparency determinants in public entities under the same general legal framework. This is the first paper that analyzes the relationship between online transparency and CG in public agencies.